Reflections on the legal framework for relations between cooperatives and subsidiaries. - Meira, Deolinda Maria Moreira Aparício (2015)
In the light of Portuguese legal system, cooperative enterprises may include an enterprise carried out by a subsidiary, provided they conform to certain requirements. The aim of this paper is to reflect on the issue of the legal framework of the relationship between the cooperative and the subsidiary. There are several problems to be addressed in this paper: (i) How to qualify such a relationship since corresponding to mere investments made by the cooperative? Should it be classified as non-member cooperative transactions or as extraordinary activities? (ii) How to qualify such a relationship when related to the development of preparatory or complementary activities for the economic activity developed between the cooperative and its members? May we speak, in this situation, of a concept of “indirect mutuality”, as provided in other legal systems? (iii) How should we classify and what is the regime of the economic results from the activity developed by the subsidiary? We will conclude, advocating: (i) That the cooperative enterprise may include an enterprise carried out by a subsidiary if this is deemed necessary to satisfy the interests of the members; (ii) The inadmissibility of the concept of “indirect mutuality”; (iii) The inadequacy of qualifying the legal relationship between the cooperative partner (iv) The application, to the economic results coming from the activity developed by the subsidiary, of the regime provided for in the Portuguese Cooperative Code to the results from non-member cooperative transactions; (v) The economic results coming from the activity developed by the subsidiary cannot be appropriated by individual co-operators members, and so should be allocated to indivisible reserves.